(untitled) (Global Journal of Science Frontier Research, 2018)
This seminar aimed to review the use of herbal growth promoting factor in poultry production which is acceptable among chicken producers to enhance productivity and control diseases. In poultry production, many alternatives have been investigated to replace antibiotics without any loss of productivity or negative influence on health. One possible way to solve this problem is searching of different plants which have positive influences on growth performance, carcass quality and cholesterol content of the blood without any residual effect on consumers. Garlic and onion are among the most popular plants widely used on the world. In farm animal’s different research had been reported on efficacy of onion and garlic as best alternatives of antibiotics in decreasing blood cholesterol, high density lipid and triglyceride, enhancing growth performances, due to, antimicrobial properties of both plants. Garlic and onion contain active ingredients, which have an ability to alter broiler performances. Being the case, Garlic and onion can replace one of the most promising alternatives to antibiotic. However, report of many outers, on dose and efficacy of both plants were not consistent. Therefore, future work will be expected to get accurate result on appropriate dose and rate of effects on broiler.